DAMPAK QUICK COUNT PILPRES 2014 TERHADAP HARGA KURS USD, ABNORMAL RETURN DAN AKTIVITAS VOLUME PERDAGANGAN SAHAM DI BEI: UJI KASUS PADA SAHAM YANG TERDAFTAR DALAM KELOMPOK PERUSAHAAN LQ-45 - Sahala Purba; Mulatua P. Silalahi (Universitas Methodist Indonesia, 2017)
The Purpose of this research is to recognize and analyze the different rate of exchange USD rate averagely abnormal return and the volume activities of trade share (TVA) on the share of LQ-45 before and after the President Election 2014 from the second to sixteenth of July 2014. This research uses event study, where is done the observation against the USD share of circulation. Averagely abnormal return and averagely the volume of share trade for 5 days before and 5 days after the President Election 2014. The method in this research uses the secondary data that is gotten from Indonesia Bank, Stock Exchange Indonesia Board, and the Capital Market of Centra Data. Data is used in this research covered with the middle USD rate of exchange, the closing daily rate of exchange, share index LQ-45, the daily volume of share trade, and number of turning share. Return expectations uses the model that is in line with market adjusted model. Mean while the samples that are used are the USD to the rate and the coming share into the table of LQ-45 in the Stock Exchange Indonesia Board. The result of research showed (1) Based on the different test statistic there is no significant difference before and after the President Election 2014 against the value of USD rate exchange averagely. (2) From the result of different test statistic averagely abnormal return share on periodic of President Election 2014. (3) While from the different test result averagely the volume of share trade (TVA) found the significant difference against the averagely volume of share trade (TVA) previously and after the President Election.